Odpowiedzi

2010-03-25T14:00:30+01:00
Zadanie 1

(x+2)/3-(x-2)/2 = 1-x |*6
2(x+2)-3(x-2) = 6-6x
2x+4-3x+6 = 6-6x
-x+10 = 6-6x
-x+6x = 6-10
5x = -4 |:5
x = -0,8


zadanie 2

-2 < (2x+1)/3 |*3
-6 < 2x+1
-6-1 < 2x
2x > -7 |:2
x > -3,5
2010-03-25T14:01:40+01:00
X+2/3-x-2/2=1-x
x-x+x=1-2/3+1
x=1 1/3


-2<2x+1/3 /*3
-6,2x+1
2x+1<-6
2x<-5-
2x<-7 /:2
x< -3 1/2
2010-03-25T14:08:34+01:00
1]
x+2/3-x-2/2=1-x
⅔-1-1=-x
-x=⅔-2
x=1⅓

poniewaz nie jestem pewna tych twoich ułamków to teraz inny zapis:
(x+2):3-(x-2):2=1-x/×6
2(x+2)-3(x-2)=6-6x
2x-3x+6x=8
5x=-4
x=-4:5
x=-0,8
2]
-2<(2x+1):3
-6<2x+1
-6-1<2x
-7<2x/:2
x>-3,5